Understanding the Reasons for Transition from Iranian Constitutional State to Authoritarian State: an Analysis in the Framework of Laclau and Mouffe’s Discourse Theory - Eltiyami Nia, Reza; Rezaei, Reza (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2021)
Throughout the history, the formation of the constitutional state has been the first experience of the modern state in Iran. The change in power relations and the restriction of authoritarian power were among the most important issues of constitutional state. The current study aims at investigating the reasons for transition from Constitutional state to an authoritarian bureaucratic state by adopting Laclau and Mouffe’s framework to political discourse analysis. Research methodology is descriptive-analytical conducted by library–based data. The results showed that the constitutional revolution transformed the power structure and traditional state, but the constitutional revolution failed to create a new order. Despite legal provisions such as the formation of the parliamentary system and the constitution, the constitutional state was unable to exercise its legal power. The co-existence of traditional and reactionary components such as the Khānins, tribal leaders, tribal populations and owners in line with modern elements, intellectuals and the heterogeneity of the ruling political elites made the constitutional revolution incapable of producing profound politico-social changes. As a result, a number of internal and external factors such as financial crisis, tribal power, the imperialist treaty of 1907,disillusionment of political elites, the formation of centrifugal forces, insecurity and global chaos and development of neighboring countries, diversity of ideological in line with geopolitical points of view have been the most important factors in the transition to the authoritarian bureaucratic state of Pahlavi and the failure of the nation – building process and the collapse of politico-constitutional system in Iran.

Na przestrzeni dziejów tworzenie państwa konstytucyjnego było pierwszym doświadczeniem nowoczesnego państwa w Iranie. Zmiana stosunków władzy i ograniczenie władzy autorytarnej należało do najważniejszych kwestii państwa konstytucyjnego. Niniejsze badanie ma na celu zbadanie przyczyn przejścia od państwa konstytucyjnego do autorytarnego państwa biurokratycznego poprzez przyjęcie ram Laclau i Mouffe do analizy dyskursu politycznego. Metodologia badań jest opisowo-analityczna, przeprowadzona na podstawie danych bibliotecznych. Wyniki analizy pokazały, że rewolucja konstytucyjna przekształciła strukturę władzy i tradycyjne państwo, ale rewolucja konstytucyjna nie stworzyła nowego porządku. Pomimo przepisów prawnych, takich jak ukształtowanie parlamentu i konstytucja, państwo konstytucyjne nie było w stanie sprawować swojej władzy prawnej. Współistnienie tradycyjnych i reakcyjnych elementów, takich jak Chaninowie, przywódcy plemienni, populacje plemienne i właściciele zgodnie z elementami nowoczesnymi, intelektualiści i heterogeniczność rządzących elit politycznych, sprawiły, że rewolucja konstytucyjna nie była w stanie wywołać głębokich zmian polityczno-społecznych. W efekcie powstało szereg czynników wewnętrznych i zewnętrznych, takich jak kryzys finansowy, władza plemienna, traktat imperialistyczny z 1907 r., rozczarowanie elit politycznych, powstawanie sił odśrodkowych, niepewność i globalny chaos oraz rozwój krajów sąsiednich, różnorodność ideologiczna w zgodzie z geopolitycznym punktem widzenia były najważniejszymi czynnikami w przejściu do autorytarnego, biurokratycznego państwa Pahlawi oraz porażce procesu budowania narodu i upadku systemu polityczno-konstytucyjnego w Iranie.
Zrozumienie powodów przejścia z irańskiego państwa konstytucyjnego do państwa autorytycznego: analiza w ramach teorii dyskursu Laclau i Mouffe’a
Keywords: nation-building; constitutional state; authoritarian state; discourse analysis; Laclau & Mouffe; budowanie narodu; państwo konstytucyjne; państwo autorytarne; analiza dyskursu; Laclau & Mouffe